The influence of populism on traditional models of creation and application of law - Publicaciones, Comisión de (2017)
The present paper seeks to make a brief exposition of the different conceptions about the idea of justice related to Law that have been given though history, from the creationist and applicable perspective of the rules. It is also a question of reflecting on the effects that populism used by political authorities in recent years has on these traditional legal models.